2019
DOI: 10.1111/jora.12541
|View full text |Cite
|
Sign up to set email alerts
|

How Adolescents Use Text Messaging Through their High School Years

Abstract: Co-construction theory suggests adolescents use digital communication to address developmental challenges. For a sample of 214 ethnically diverse adolescents, this research used direct observation to investigate the frequency, content, and timing of texting with parents, peers, and romantic partners through grades 9-12. Analyses showed that texting frequency follows a curvilinear trajectory, peaking in eleventh grade. Adolescents discussed a range of topics, predominantly with peers. Communication with parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 64 publications
3
47
0
Order By: Relevance
“…These researchers collected all text messages exchanged (with all relationship partners, including parents) by about 200 adolescents over their entire high school careers (2008)(2009)(2010)(2011)(2012). The researchers used a qualitative hand-coding approach to capture antisocial content (e.g., discussions about drugs, aggression, or rule-breaking), negative talk (e.g., negative social interactions, social exclusion, negative appraisals of self or others, expression of negative affect, and sarcasm), positive talk (e.g., discussion of positive events or feelings, positive assessment of self or others), and sexual content (e.g., references to past, present, or future sexual behavior) in text messages taken from 4 days per year (across 4 years) for each adolescent (interrater reliabilities (kappa) ranged from 0.65 to 0.82 across codes; Ehrenreich et al 2020). Results indicate that teens text far less with parents than with peers; the average participant exchanged 27.58 (SD = 27.73) text messages with parents across 4 days in the 12th grade (which comprise about 6.45% of all texts exchanged; SD = 8.65).…”
Section: Text Messaging and Digital Analogues To Autonomy And Relatedness In Emerging Adulthoodmentioning
confidence: 99%
“…These researchers collected all text messages exchanged (with all relationship partners, including parents) by about 200 adolescents over their entire high school careers (2008)(2009)(2010)(2011)(2012). The researchers used a qualitative hand-coding approach to capture antisocial content (e.g., discussions about drugs, aggression, or rule-breaking), negative talk (e.g., negative social interactions, social exclusion, negative appraisals of self or others, expression of negative affect, and sarcasm), positive talk (e.g., discussion of positive events or feelings, positive assessment of self or others), and sexual content (e.g., references to past, present, or future sexual behavior) in text messages taken from 4 days per year (across 4 years) for each adolescent (interrater reliabilities (kappa) ranged from 0.65 to 0.82 across codes; Ehrenreich et al 2020). Results indicate that teens text far less with parents than with peers; the average participant exchanged 27.58 (SD = 27.73) text messages with parents across 4 days in the 12th grade (which comprise about 6.45% of all texts exchanged; SD = 8.65).…”
Section: Text Messaging and Digital Analogues To Autonomy And Relatedness In Emerging Adulthoodmentioning
confidence: 99%
“…A third limitation is that our reasons for texting were global and did not differentiate between texting with friends, romantic partners, parents, or other family members. Adolescents tend to text about negative emotions and events more frequently with their peers than with their parents (Ehrenreich et al, 2020); thus, future studies may consider whether motives for texting vary depending on the texting partner. Fourth, our questions focused on motivations for texting and did not ask questions about reasons for replying to texts (e.g., respond to friend's negative emotions or need for help).…”
Section: Limitationsmentioning
confidence: 99%
“…According to the uses and gratifications theory, individuals use media in order to fulfill certain needs (Rubin, 2009). For young adults and adolescents, texting can be used for a variety of purposes such as discussing positive and negative events, showing affection, relaxing, coordinating offline activities, and discussing schoolwork (Jin and Park, 2010;Lenhart et al, 2010;Grellhesl and Punyanunt-Carter, 2012;Ehrenreich et al, 2020). It is possible that there are different patterns of texting use.…”
Section: Introductionmentioning
confidence: 99%
“…Second, adolescents in this study may have experienced more opportunities for prosocial behavior as a result of the pandemic, such as helping, caring for, and comforting friends and family members; prosocial behavior is associated with positive adjustment [ 46 ]. Last, adolescents have a demonstrated ability to use technology to navigate developmental and mental health challenges; in our study, adolescents may have found entertainment, support, and distraction through digital interaction, such that any effects of COVID-19 on mental health were mitigated [ 47 ].…”
Section: Discussionmentioning
confidence: 99%